PENGARUH LINGKUNGAN KERJA DAN PERILAKU PEMIMPIN TERHADAP STRESS KERJA SERTA DAMPAKNYA PADA TURNOVER INTENTION (STUDI KASUS PADA ANGGOTA TEMBALANG KULINER) - Anoki Herdian Dito (Applied Research in Management and Business, 2022)
The purpose of this research is to investigate the effect of work environment and leader behavior on work stress and turnover intention. The study was conducted at community of Tembalang culinary (Komunitas Tembalang Kuliner), with 184 employees as a respondent who work in 35 culinary places. All data is processed using Structural Equation Models (SEM) which assisted by application program of Analysis of Moment Structure (AMOS) 21.0 version. According to the analysis, it is concluded as the followings: work environment has a positive effect on work stress; leader behavior has a positive effect on work stress; and work stress has a positive effect on turnover intention.